Influence of Surrounding Land Use on the Physicochemical Parameters of Agulu Lake, Anambra State, Nigeria - Nelson Mbanefo Okoye; Louis Chukwuemeka Orakwe (Archives of Current Research International, 2018)
Effective surface water management requires a detailed understanding of the relationship between land use and water quality. This study investigated the spatial variability of land use impacts on water quality of Agulu Lake in Anambra State, Nigeria. The aim was to look at how the diverse land use types around the lake environment affect pollutant load of the lake. Water samples were collected from six locations within the lake corresponding to the identified land uses in the study area in February and June 2016. Ten physicochemical parameters comprising pH, temperature, EC, turbidity, DO, BOD, TSS, NO3--N, PO43- and SO4 were analyzed using standard methods and compared with WHO standards. The results show that except for pH, the prevailing season influenced the other parameters. EC, turbidity, DO, BOD, TSS, NO3--N, PO43- and SO4 values were higher in the wet season. There was significant variation in the physicochemical parameters related to different land-use patterns. Water samples from industrial, residential and recreational areas, and the area receiving runoff from transportation were found to have the highest levels of pollutant concentrations.